Сement based compositions with complex modifying additives based on glyoxal - A. I. Kudyakov; A. S. Simakova; A. B. Steshenko (Вестник СибАДИ)
Introduction. Due to the multicomponent composition, cement based concrete has a high potential for improving technical characteristics by controlling technological processes or the quality of raw materials, which makes it possible to develop composites with specified requirements for the construction of modern resource and energysaving buildings, including for the northern territories of Russia. With the transition to the micro level of the formation of the structure of cement based concretes, new opportunities open up for the directed regulation of properties. Based on this, in order to improve the quality of concrete by improving the structure of the hardened cement paste, a method was proposed for introducing modifiers into the mixture, which directly affect the new growths in the ‘cement-water’ system, which makes it possible to control the process of structure formation of the hardened cement paste.Materials and methods. Research has been carried out using test methods set out in national standards and physical and chemical analysis: thermal analysis and scanning electron microscopy. The results of a study of the effect of complex modifying additives (CMA) based on an aqueous solution of glyoxal and organic acids on the rheological and strength properties of hardened cement paste are presented, the regularities of the processes and the mechanism of structure formation of the modified cement paste are determined.Results. The optimal compositions of a cement based composition based on an aqueous solution of glyoxal have been determined. On the first day of hardening of hardened cement paste with CMA, including polylactic acid and an aqueous solution of glyoxal, as well as lactic acid and an aqueous solution of glyoxal, the strength increases by 23.5%, and at 28 days of age - up to 63% compared to the control composition. Physicochemical studies found that in hardened cement paste with CMA based on an aqueous solution of glyoxal and organic acids, the density and homogeneity of the structure increases, and the content of low-basic hydrosilicates also increases.Conclusion. The developed complex additives are recommended for use in the production of cement based concretes with the required rate of structure formation and high strength.